Consumer cash usage: A cross-country comparison with payment diary survey data - John Bagnall; David Bounie; Kim P. Huynh; Anneke Kosse; Tobias Schmidt; Scott Schuh; Helmut Stix (Bank of Canada, 2014)
We measure consumers' use of cash by harmonizing payment diary surveys from seven countries. The seven diary surveys were conducted in 2009 (Canada), 2010 (Australia), 2011 (Austria, France, Germany and the Netherlands), and 2012 (the United States). Our paper finds cross-country differences - for example, the level of cash usage differs across countries. Cash has not disappeared as a payment instrument, especially for low-value transactions. We also find that the use of cash is strongly correlated with transaction size, demographics, and point-of-sale characteristics such as merchant card acceptance and venue. – – Les auteurs mesurent l'usage des espèces en harmonisant les données de journaux d'achats tenus par les consommateurs de sept pays. Les journaux d'achats proviennent d'enquêtes administrées en 2009 (Canada), 2010 (Australie), 2011 (Allemagne, Autriche, France et Pays-Bas) et 2012 (États-Unis). L'étude montre qu'il existe des differences entre pays : par exemple, le niveau d'usage des espèces varie d'un pays à l'autre. Les espèces n'ont pas disparu en tant que moyen de paiement, en particulier pour les achats de faible valeur. Les auteurs constatent également que l'usage des espèces est fortement corrélé avec la valeur de l'achat, les caractéristiques individuelles et les caractéristiques du point de vente telles que l'acceptation de la carte de paiement et le type de commerce.
Keywords: E41; D12; E58; 330; Bank notes; Econometric and statistical methods; Financial services; E-money